ANALISIS FESTIVAL CAP GO MEH PADA PENDAPATAN SEKTOR USAHA KULINER DI KOTA SINGKAWANG - Andria, Priska Deby; Syahrudin, Husni; Kuswanti, Heni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2025)
This study was conducted to determine the impact of the Cap Go Meh Festival on income in the culinary business of the Singkawang City community and the supporting and inhibiting factors of the Cap Go Meh Festival that have an impact on income. This research uses a qualitative approach and case study. Interviews and documentation were used as data collection tools. Seven food vendors who sell during the Cap Go Meh Festival in Singkawang City became the main informants of the research, and one supporting informant, namely the Head of the Tourism Division of the Tourism, Youth and Sports Office of Singkawang City. Based on the results of the study, culinary businesses in Singkawang City benefited from this Festival. Culinary business income, increased production, additional employees, and economic involvement of local communities are some examples of impacts that can be seen. The main factors that support each other to create a sustainable and thriving business environment during the festival are government support, high visitor numbers, effective cultural promotion, tourist attendance, and the right location. Factors such as weather, visitor safety and intense competition are some of the barriers that can affect the income of Singkawang City's culinary industry during the Cap Go Meh festival. Nonetheless, the Cap Go Meh festival has the potential to boost Singkawang City's overall economy, as businesses and people living nearby benefit.